Calcium intake and its relationship with risk of overweight and obesity in Adolescents - Goldberg, Tamara Beres Lederer [UNESP]; Da Silva, Carlo Cristiane [UNESP]; Peres, Luciano. Natal Lopes [UNESP]; Berbel, Marina Nogueira [UNESP]; Heigasi, Márcia Braz [UNESP]; Ribeiro, Josy Maria Cabral [UNESP]; Suzuki, Karina [UNESP]; Josué, Liene Mílcia Aparecida [UNESP]; Dalmas, José Carlos [UNESP] (My University, 2009)
Adolescents' eating habits are determined by social, psychological, economic, political, and educational influences. They tend to prefer foods with inadequate nutritional value and high fat and carbohydrate content which leads to excessive weight gain and for many, calcium intake is restricted. According to some authors, low calcium intake is linked to increased adiposity. The objective was to evaluate adolescent calcium intake and investigate a possible relationship between calcium intake and nutritional state. As part of their first consultation at Botucatu Adolescent Outpatient Clinic - UNESP, 107 adolescents were nutritionally classified by BMI, according to age, gender, and bands proposed by CDC and AAP. Diet was evaluated by a 3 day 24h food recall, adopting 1300mg/day calcium intake as recommended by Dietary Reference Intakes. Median calcium intake for the whole sample was 546.6mg/day, with 91.30% female and 86.84% male presenting lower than adequate daily recommended ingestion levels (DRI). There was significant difference between calcium densities (Ca mg/1000kcal) in eutrophic and overweight/obesity in males. Male adolescents showed an inverse relationship between calcium intake and adiposity (r = -0.488 and p=0.0173), which corroborates the hypothesis that low calcium intake is linked to fatty tissue gain. Only 8.70% of female and 13.16%' of male adolescents reached their daily recommended calcium intake levels. It must therefore be stressed that nutritional education is an important protection factor for children and adolescents in later life.
Keywords: Adolescence; Bone health; Calcium intake; Obesity